Culture as cure? The protective function of Māori cultural efficacy on psychological distress - Muriwai EM; Houkamau CA; Sibley CG (New Zealand Psychological Society)
Māori, the indigenous peoples of New Zealand, continue to experience health disparities in comparison to other ethnic groups. Previous research suggests Māori who affiliate jointly as Māori and Pākehā (New Zealand European) tend to experience different psychological outcomes than those who solely identify as Māori. Using a culturally-specific approach we propose and test an Efficacy-Distress Buffering Model, which posits that high levels of Māori Cultural Efficacy should have a buffering function, protecting Māori against Psychological Distress (N = 632). Our findings indicate that Māori with a higher level of Cultural Efficacy showed greater psychological resilience. In contrast, increased rates of psychological distress were documented amongst those who were lower in Cultural Efficacy and this effect was most pronounced among individuals who identified solely as Māori. Our results support a ‘culture-as-cure’ perspective and indicate that increased Māori Cultural Efficacy has a direct protective effect for those who may be at risk of negative psychological outcomes and associated risk factors.
Keywords: 1701 Psychology; 1702 Cognitive Sciences